Poetic Biography of G.-Zh. Tuguldurov (1817-1872), the Vth Abbot of Aginsky Datsan Dechen Lhundupling - Bair L. Tushinov; Soelma R. Batomunkueva; Vladimir V. Hartaev (Монголоведение)
Introduction. TThe article is devoted to the study of the poetic namthar — the biography of the Vth abbot of the Aginsky datsan Dechen Lhundupling Galsan-Zhimba Tuguldurov. The purpose of the study is analysis and introduction of this biography into scientific circulation. A previously unexplored manuscript of a Tibetan-language namthar from the collections of the Aginsky datsan was the object of the research. A copy of this manuscript “Seeds of the biography of the abbot of the monastery Dechen Lhundupling Choje Kelsang Jinpa Pelsangpo” (Tib. bde chen lhun grub gling gi khri pa chos rje skal bzang spyin pa dpal bzang po'i rnam thar gyi sa bon bzhugs) by unknown author was kindly given to us by the fund custodian D.V. Vakunin. The chronological scope of the source covers the period from 1817 to 1872. The relevance of this work is caused by the need of introducing this source into scientific circulation due to the fact that despite the significance of the personality of G.-Zh. Tuguldurov in the history of Buryat Buddhism, information about him and his works have not yet been fully researched. As a result of the study, new historical facts of the biography of G.-Zh. Tuguldurov were revealed; the names of his Mongolian teachers were established; a description of his contribution to the development of Buddhism in the Aginsky and Tsugolsky monasteries was given; the circumstances of G.-Zh Tuguldurov’s passing from life were described; founded was an unidentified earlier as his work a Sanskrit-Tibetan dictionary “Sanskrit-Tibetan dictionary with explanations compiled by Choje Tri-Rinpoche”.